Leadership-The Most Important Area of Educational Performance - Seema Bhakuni (Ilomata International Journal of Management, 2022)
Leadership is seen as the most critical aspect in successfully developing educational institutions, supporting stated aims and objectives, and enhancing education. It is a vital aspect in determining whether an organization succeeds or fails. A leader's style is defined by how he guides and encourages others to accomplish institutional objectives. Basic skills are described as "a collection of psychological and social areas of expertise and interpersonal skills that enable individuals to make informed choices, resolve issues, think critically and analytically, effectively communicate, develop relationships, empathize with others, and cope and enhance their quality of life, productively and healthily." This research aims to determine the effect of Leadership as a practical skill on educational establishments. From the perspective of the school, the principal's Leadership is critical. His function and responsibilities will impact all facets of the school organization’s life. At the executive level of the school, the principal's Leadership is the significant variable that serves as a bridge between individual lives and the future outlook of any institution. This research aims to demonstrate how Leadership as a practical skill, affects educational institution’s performance. This is a conceptual study that provides a theoretical foundation for the notion. The reports and findings indicate that leadership style plays a critical role in boosting an institution's success since it influences the organization's culture and the value of its personnel.